2013
DOI: 10.1182/blood-2013-01-480665
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune control of EBV-infected B cells by invariant natural killer T cells

Abstract: Key Points• B cells rapidly downregulate CD1d expression after EBV infection, thus abrogating iNKT cell recognition.• EBV-infected B cells induced to express CD1d elicit iNKT cell functions even in the absence of exogenous antigen.Individuals with X-linked lymphoproliferative disease lack invariant natural killer T (iNKT) cells and are exquisitely susceptible to Epstein-Barr virus (EBV) infection. To determine whether iNKT cells recognize or regulate EBV, resting B cells were infected with EBV in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 54 publications
4
99
0
2
Order By: Relevance
“…iNKT cells are, like lymphocytes, innate, able to activate and produce large quantities of cytokines rapidly and have also been shown to have cytotoxic properties [10]. They are known to play an important role in both acute [11] and chronic viral infections [14,28], including a recent report on their role in dengue infection [12]. Acute dengue is known to associate with a marked lymphopenia [29], especially with reduction of T cells due to massive T cell apoptosis [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…iNKT cells are, like lymphocytes, innate, able to activate and produce large quantities of cytokines rapidly and have also been shown to have cytotoxic properties [10]. They are known to play an important role in both acute [11] and chronic viral infections [14,28], including a recent report on their role in dengue infection [12]. Acute dengue is known to associate with a marked lymphopenia [29], especially with reduction of T cells due to massive T cell apoptosis [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that TLR9-induced miR-155 could be one reason for the downregulation of CD1d. TLRs recognize different types of components from microbes, and EBV can reduce the expression of CD1d in B cells [12]. Thus, the dsDNA of EBV may induce the upregulation of miR-155 and the corresponding downregulation of CD1d in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…A viral infection could downregulate the expression of CD1d [11,12]. However, the effect of cytosine guanine dinucleotide (CpG) on the expression of CD1d in B cells is unclear.…”
Section: Stimulation Of Tlr9 Ligand Cpg Decreases Cd1d Levels In B Cellsmentioning
confidence: 99%
See 2 more Smart Citations